Pengaruh Pendapatan dan Biaya Operasional terhadap Laba Bersih - Mutiara, Pipit (J-MAS (Jurnal Manajemen dan Sains), 2022)
In determining the profits, operational cost is the expense incurred during the process of operating activities of the company, which is included into the criteria and the principle of the determination of income that need to be determined by the company. Operating expenses include general and administrative costs as well as cost of sales. This study aims to determine whether there is influence of income and operating expenses to net income. The research method uses descriptive and verification method with quantitative approach. The results of this study showed that partial earnings affect net income, and operating expenses effect is inversely proportional to the net profit, while simultaneously the income and the effect on operating costs net profit.